Membangun Sinergi Global: Upaya IAI Almuslim Aceh dalam Peningkatan Kualitas Pendidikan melalui Kerja Sama Internasional - Ghani, Abdul; Diana, Diana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2023)
International programs are a vital strategy for expanding the participation of academic and non-academic communities in global mobility activities, supporting the implementation of the Tridharma of Higher Education. In this context, Institut Agama Islam (IAI) Almuslim Aceh organized an international program in Malaysia from June 11-14, 2023, to strengthen academic cooperation and community service. An action research approach was employed as it allows researchers to directly intervene and observe the changes occurring during the collaboration program. Data collection techniques included direct observation, in-depth interviews, and documentation. The collected data were analyzed through the steps of grouping, categorizing, and interpreting the data. This study utilized an evaluative approach based on the CIPP model (Context, Input, Process, Product). The results of this program indicated an increase in the knowledge and awareness of Indonesian citizens regarding the importance of applying knowledge appropriately according to social contexts and development needs. Additionally, the signing of a Memorandum of Understanding (MOU) with Universiti Sulthan Azlan Shah in Malaysia resulted in student and faculty exchange programs aimed at enhancing educational quality and broadening the global perspectives of the participants. Collaboration in an international conference with Universiti Malaya created opportunities for knowledge and cultural exchange, as well as strengthened cross-cultural cooperation in education and research. The implications of this program are the strengthening of institutional capabilities in implementing the Tridharma of Higher Education internationally, as well as the improvement of education quality and future global cooperation.